The role of McKinsey's organizational diagnosis model in reducing internal tax risks : Applied research (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to define organizational diagnosis as one of the important tools in improving tax performance through the use of one of its most important models represented by the McKinsey S7 model with seven dimensions that include (strategy, organizational structure, employees, leadership, skills, systems, shared values). The role of this model in reducing internal tax risks represented by (tax assessment risks, information systems risks, tax audit risks, administrative risks, tax collection risks, employee risks, and regulatory risks). The research problem was represented in reducing internal tax risks. The research problem emerged with the following question: (Does the McKinsey model for organizational diagnosis play a role in reducing internal tax risks in the General Tax Authority?) The current research aims to shed light on the McKinsey model for organizational diagnosis as an independent variable and internal tax risks as a dependent variable. Therefore, the importance of the research comes from the fact that it sheds light on improving the tax performance of the reality of the Authority’s work through the McKinsey model and its importance in providing a decent work environment, based on the importance of the research topic for the economic unit being studied, which is the General Tax Authority. Whereas the descriptive analytical approach was used, based on the reality of the General Tax Authority, the research sample was at the headquarters of the General Tax Authority for the years (2021, 2022, 2023). From the frameworks of discussing the results, the researchers reached a number of results, the most important of which is that the organizational diagnosis through its models, the most important of which is the McKinsey model, is an effective strategic tool for identifying and analyzing the gaps in the tax system of the General Tax Authority by examining the tax operations and procedures, and it identifies the potential errors that expose the Authority to tax risks. The researchers also presented a number of recommendations, the most important of which is the periodic application of the McKinsey model for organizational diagnosis of tax operations in the General Tax Authority, which helps discover errors or loopholes early and corrective action can be taken before it affects the entire tax system.